Incidence of a New Pest, the Cotton Mealybug Phenacoccus solenopsis Tinsley, on Sesame in North Ethiopia - Zenawi Gebregergis (International Journal of Zoology)
Sesame (Sesamum indicum) is one of the most important cash crops grown extensively for its seeds in Ethiopia. Production of sesame in the country is very crucial in many aspects, but the invasion of the cotton mealybug, Phenacoccus solenopsis Tinsley, is becoming a big deal in its production. A survey for mealybug infestation was conducted during 2016 production season in 15 localities of “Kafta Humera” district so as to assess the incidence and severity of the pest. In each locality 2 sesame farms have been selected and 6 samples per farm (2 samples from the road sides, 2 from camp surrounding, and 2 from the central part of the farms) have been checked. During the survey, “Bowal” and “Sherif Hamad” have scored the higher incidence and severity of mealybugs. Road sides and camp surrounding of the farms were shown to have severe infestation. Stony and oxen plowed farms were also intensively invaded with cotton mealybugs. The pest has different natural means to infest new areas; thus its control measure has to be developing timely.